The role of biocatalysis in green and sustainable chemistry - Teixeira, Iris S. [UNESP]; Souza, Thais R. [UNESP]; Milagre, Humberto M.S. [UNESP]; Milagre, Cintia D. F. [UNESP] (De Gruyter, 2022)
Biocatalysis is well recognized as a greener tool for organic synthesis with many successful ongoing industrial processes. Additionally, besides the research component, it can be used in outreach activities and the Chemistry and Chemical Engineering curriculum to introduce and discuss green and sustainable chemistry. An overview of the Brazilian chemical sector's contribution to the UN sustainable goals is also provided.
Keywords: Biocatalysis; Sustainable chemistry